Pemeriksaan Cemaran Kapang Pada Udara Dan Pakaian Santri Di Salah Satu Pondok Pesantren Surabaya Timur - Anindita Riesti Retno Arimurti; Fitrotin Azizah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
Dormitory is a place for student who built in various small scales to a very large scale. Of the many dormitory residents with bad space such as lack of ventilation and incoming sunlight, the large number of scattered students' clothes causes the room to become damp. The presence of air mold is caused by the lack of ventilation as well as the humidity of the room environment in the dormitory which can cause several diseases, one of which is ARI. The purpose of this study was to determine whether or not there is mold contamination on air in the room and clothes of the students at one of the Islamic boarding schools in East Surabaya. This type of research is descriptive. The sample used is air in several dormitory rooms at one of the Islamic boarding schools in East Surabaya. This research method uses the isolation technique of Sabauraud Dextose Agar (SDA) media which is partially opened and then placed in several rooms in this Islamic boarding school. Second, 30 samples of clothes were taken randomly from students from different disciplines and then scratched on SDA media. In the results of macroscopic observations, of the 30 sampled rooms. Microscopic colonies of cotton taken from the media showed positive results for hyphae, mycellium, spores, and conidiospores. The results obtained were positive there were Aspergillus sp. with the percentage was 100% while the results of the students' clothing swabs, from 30 clothing samples found 80% positive for mold contamination.